1988
DOI: 10.1002/eji.1830180204
|View full text |Cite
|
Sign up to set email alerts
|

Clonal heterogeneity of HLA-B27 cellular allo-recognition. Delineation of immunodominant sites

Abstract: The fine specificity of nine cytolytic T lymphocyte (CTL) clones obtained after stimulation of HLA-B27- responder lymphocytes with B27.1+ lymphoblastoid cell lines has been analyzed. These clones defined three different reaction patterns when tested against a panel of target cells including those expressing all known HLA-B27 subtypes: (a) specific recognition of HLA-B27.1, B27.2 and B27d, (b) selective reactivity with B27.1, B27d and HLA-B40 and (c) selective recognition of B27.1, B27.2, B27d, B27f and B40. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Comparison of the sequence profiles of the peptide pools from B'2701 to B~ suggests that B27 subtypes share a significant number of bound peptides, but many R2containing peptides either bind to only some subtypes or they bind to all the subtypes but with greatly different efficiency. This is in agreement with functional studies showing frequent crossreactivity, but also differential recognition, of HLA-B27 subtypes with anti-B~ CTL (14,23). Substantial differences among peptide pools from two HL.A-A2 subtypes have also been recently reported (24).…”
Section: Discussionsupporting
confidence: 89%
“…Comparison of the sequence profiles of the peptide pools from B'2701 to B~ suggests that B27 subtypes share a significant number of bound peptides, but many R2containing peptides either bind to only some subtypes or they bind to all the subtypes but with greatly different efficiency. This is in agreement with functional studies showing frequent crossreactivity, but also differential recognition, of HLA-B27 subtypes with anti-B~ CTL (14,23). Substantial differences among peptide pools from two HL.A-A2 subtypes have also been recently reported (24).…”
Section: Discussionsupporting
confidence: 89%
“…In previous studies we have established the fine specificity of a series of anti-B27 CTL clones derived from individual PA in this and other experiments 19,10,191. On the bases of the some individual anti-B27 CTL clones is abrogated by changes located at opposites ends of this site, such as residues 59 and 152 [9,10 Similar observations have been reported for some anti-H-2K alloreactive CTL clones that fail to recognize somatic mutants with changes located far apart on the surface of the peptide-binding groove [34].…”
Section: Discussionmentioning
confidence: 95%
“…In previous studies we have characterized a series of alloreactive CTL clones derived from a single B27-individual after stimulation with B*2705+ (B27.1') cells [9,10,191. A common feature of these clones was their lack of recognition of those HLA-B27 subtypes with a change at residue 152 (B*2704 and B*2706) as well as their lower or null recognition of B*2702, with changes at positions 77,80 and 81 with respect to B*2705.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the serological cross-reactivities between HLA-B27 and -B40 are known. 13 Other HLA-B27 cross-reactive haplotypes are -B7, -B42, and -B60, which are all known frequently to be positive in patients with -B27-negative ReA in the United States and in Europe. Robinson et al 14 reported a high incidence of -B40 in HLA-B27-positive ankylosing spondylitis patients in the United States.…”
Section: Discussionmentioning
confidence: 99%